Percutaneous coronary intervention in the elderly: Results from the Thai National Percutaneous Coronary Intervention Registry (TPCIR) - Songsak Kiatchoosakun (2018)
Aims: The objective of this study was to evaluate the outcomes and identify the risk factors of in-hospital mortality among elderly patients undergoing PCI in Thailand. Methods and results: Included in this study were 4,156 consecutive patients (comprising 639 elderly [age W75 years] and 3,517 non-elderly [age <75 years]) undergoing PCI between May 2006 and October 2007. The success rate of PCI was less favourable among elderly compared to the non-elderly patients (91.2% vs. 87.5%; p=0.003). Elderly patients had higher rate of post PCI renal failure (3.9% vs. 1.8%; p=0.001), Q-wave myocardial infarction (3.0 vs. 1.4%, p=0.003), and unadjusted in-hospital mortality (5.3% vs. 2.4%, p≤0.001), compared with non-elderly patients. After adjustment for baseline variables, acute coronary syndrome and heart failure were the two variables most associated with increased mortality (OR=5.95, 95% CI=3.22-11.01), p<0.001 and OR=5.73,95% CI=3.80-8.63), p<0.001, respectively). According to the multivariate analysis, age was not significantly related with increased mortality (OR=1.37, 95% CI=0.87-2.16, p=0.174). Conclusions: Our study highlights the safety and effectiveness of PCI in elderly patients since advanced age is not a predictor of in-hospital mortality. © Europa Edition 2010. All rights reserved.